Perspective of Overhauser dynamic nuclear polarization for the study of soft materials. (January 2018) - Biller, Joshua R.; Barnes, Ryan; Han, Songi
Abstract: Solution state Overhauser dynamic nuclear polarization (ODNP) has been studied for 60 years, but only in recent years has found applications of broad interest to biophysical sciences of hydration dynamics (HD-ODNP) around biomolecules and surfaces. In this review we describe state-of-the-art HD-ODNP methods and experiments, and identify technological and conceptual advances necessary to broadly disseminate HD-ODNP, as well as broaden its scope. Specifically, incomplete treatment of the saturation factor leads to the use of high microwave powers that induce temperature-dependent effects in HD-ODNP that can be detrimental to the stability and property of the sample and/or data interpretation, and thus must be corrected for. Furthermore, direct measurements of the electron spin relaxation times for the nitroxide radical-based spin labels used in HD-ODNP have recently caught up with the ambient solution conditions of relevance to HD-ODNP experiment, allowing us to envision an explicit treatment of the saturation factor. This would enable "single-shot" HD-ODNP at one or two concentrations and power levels, cutting down experimental times from the typical hours to minutes. With the development of a user-friendly and robust operation, the application of HD-ODNP experiments can be broadened for the study of biomolecules, biomaterials, soft polymer materials (i.e. hydrogels) and surfaces. In fact, any hydrated materials that can be viably spin labeled can yield information on local water dynamics and interfaces, and so guide the design of soft materials for medical and pharmaceutical uses. A brief introduction to spin-labeling, and exemplary applications to soft materials is discussed to serve as inspiration for future studies. Graphical abstract: Over the past 10 years, much progress has been made in the application of solution Overhauser dynamic nuclear polarization (ODNP) for the study of hydration dynamics in biomolecules. In this review, we comment on that work, and further aspects of the technique to be refined. ODNP is a powerful tool which can also be applied to the study of hydration dynamics in soft polymer materials. Unlabelled Image Highlights: Overhauser DNP study of hydration dynamics (HD-ODNP) is now established as a quantitative tool to study biological water. Explicit treatment of the saturation factor enables "single shot" HD-DNP reducing sample heating and long experimental time. HD-ODNP of biomolecules informs analysis of soft polymer/hydrated materials used in medical and pharmaceutical applications.